Geophysical and remote sensing methodologies applied to the analysis of regolith and geology in Burkina Faso, West Africa - (:unkn) unknown (My University, 2011)
The oldest parts of continents, so-called cratons, are the focus of worldwide research not only because they represent primary constraints for our understanding of the early evolution of the Earth, but also because of their significant mineral potential. This work contributes to the understanding of the geological and geomorphological evolution of the West African Craton, by an integrated analysis of airborne geophysical and satellite remote sensing data constrained by field structural, lithological, geophysical, and geomorphological observations acquired around Houndé, Boromo and Banfora greenstone belts and associated granitoid domains in western Burkina Faso. The results of this integration suggest that the granitoid domains of western Burkina Faso are formed by numerous small- to medium-sized plutons, and the magnetic data provided a better definition of the actual pluton shapes. Airborne gamma ray spectrometry data aided in the mapping process in areas with less regolith cover. Three deformation events (D1-D3) can be distinguished in western Burkina Faso. A megacrystic tholeiitic basalt unit allowed us to establish stratigraphic correlations between the two belts and propose a crustal scale anticline (D1). The D1 penetrative structures, resulting from an E-W to WNW-oriented compression are generally overprinted by the D2 transcurrent shear zones, which is well visible in the magnetic data. Previously unreported and already known S2 shear zones represent prospective areas for gold exploration. The regional-scale system geometry was controlled by coaxial shortening of stiffer volcanic units and coeval magma input. The last D3 N-S compression is either late-Eburnean or perhaps even Pan-African. The mineralogical composition of rocks and derived regolith surfaces may be assessed by visible and infrared spectroscopy. A new spectral library has been acquired consisting of in situ and laboratory 0.35 µm to 2.5 µm spectra of rocks and derived regolith
Keywords: African Research